11=2m+6-5

Simple and best practice solution for 11=2m+6-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=2m+6-5 equation:


Simplifying
11 = 2m + 6 + -5

Reorder the terms:
11 = 6 + -5 + 2m

Combine like terms: 6 + -5 = 1
11 = 1 + 2m

Solving
11 = 1 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
11 + -2m = 1 + 2m + -2m

Combine like terms: 2m + -2m = 0
11 + -2m = 1 + 0
11 + -2m = 1

Add '-11' to each side of the equation.
11 + -11 + -2m = 1 + -11

Combine like terms: 11 + -11 = 0
0 + -2m = 1 + -11
-2m = 1 + -11

Combine like terms: 1 + -11 = -10
-2m = -10

Divide each side by '-2'.
m = 5

Simplifying
m = 5

See similar equations:

| .75x+.5y=25 | | -3+11=-8v+51 | | -(4x-6)-6(6x-4)= | | 4y-2y=-4-12 | | 25x^2+10x-11=0 | | 7x-(3x+1)=5-(4x-8) | | 17-×/4=-10 | | (x^5.5)/(x^0.5) | | 2(6x-6)+6(5x-5)= | | v/6=8/7 | | x/(1-2X)=5 | | 119-x=162 | | 1/27*x^3=m*x | | 5u-8=47 | | 4/x-6=5 | | 4x+5=-8-9x | | x-.95=.75 | | -1/9x^3=m*k | | 3(t-6)+7t=5(2t+4)-12 | | 4x^2+12-2=0 | | 4x+44y=-8 | | 4x+x+1=7x-21 | | 6a^3-3a^2+8a-4= | | 43/86 | | 3.1x-1.3=4 | | 1/3x-4=1/2 | | 4u^5+22u^4+10u^3=0 | | 6x+(x-8)= | | -7x+17=-67 | | 6y+40=2x | | 6x+10=5+5x | | 4+6x=3x-29 |

Equations solver categories